An amputated ovary in a girl: A rare case report and review of the literature - Bakal, Ünal; Saraç, Mehmet; Tartar, Tugay; Kazez, Ahmet (Logos Medical Publishing, 2011)
Amputated ovary is a rare cause of abdominal calcification in girls. Up to date, 11 cases had been reported. A calcified amputated ovary was found in a 9-year-old girl by laparoscopy. The most likely explanation is subclinical torsion of the adnexa with subsequent amputation, necrosis, and calcification. This rare entity should be considered in the differential diagnosis of pelvic calcification in girls. In this study, we present a rare case and brief review of the literature. © 2011 Logos Medical Publishing . All Rights Reserved.
Kiz çocu?unda kopmuş over: Ender bir olgu sunumu ve literatür taramasi
Keywords: Amputated; Calcified; Children; Ovary; Torsion